Pengaruh Leverage, Size, Growth dan Profitabilitas Terhadap Nilai Perusahaan - Vany Febri Rianti; Barlia Annis Syahzuni (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This research was conducted with the aim of seeing the results of partial tests on how leverage, size, growth, and profitability impact firm value. This study uses debt to equity ratio to assess leverage, LN total assets to measure size, net profit after tax to measure growth, and net profit margin to measure profitability in this study as independent variables. Firm value is proxied by stock price to book value as the dependent variable. The study focused on a population of 67 infrastructure entities listed on the Indonesia Stock Exchange (IDX) in 2021-2023. This study uses a causal relationship with a purposive sampling technique, namely sampling with certain criteria. There were 78 samples from 26 entities after being eliminated based on sample criteria. This research uses a multiple linear regression analysis method. Data processing carried out shows that leverage, size, and profitability have a partial effect on firm value. While firm value is not partially affected by growth.